Light Leakage of Multidomain Vertical Alignment LCDs Using a Colorimetric Model in the Dark State - Chuen-Lin Tien; Rong-Ji Lin; Shang-Min Yeh (Advances in Condensed Matter Physics)
Light leakage from liquid crystal displays in the dark state is relatively larger and leads to a degraded contrast ratio and color shift. This work describes a novel colorimetric model based on the Muller matrix that includes depolarization of light propagating through liquid crystal molecules, polarizers, and color filters. In this proposed model, the chromaticity can be estimated in the bump and no-bump regions of an LCD. We indicate that the difference between simulation and measurement of chromaticity is about 0.01. Light leakage in the bump region is three times that in no-bump region in the dark state.